The DEVELOPMENT OF MULTIMEDIA LEARNING BASED ON GUESSING IMAGE GAMES IN CLASS V ECOSYSTEM MATERIALS OF SDN MRICAN 1 - Billa Setya Putri, Arna; Wahyudi , Wahyudi; Sahari, Sutrisno (Institut Agama Islam Ngawi, 2023)
Abstract: This research was motivated by problems in the use of instructional media in science learning on ecosystem material at SDN Mrican I. The purpose of this study was to develop learning multimedia based on a picture guessing game on ecosystem material for fifth grade students at SDN Mrican 1. This study used the ADDIE development model which has five stages including: Analysis, Design, Development, Implementation, and Evaluation. The quality of this research is seen from the level of validity, practicality and effectiveness of the product being developed. As for the results of research and development related to data validation results of media experts scored 91.7%, while validation by elementary science material experts obtained a score of 87.5%, the average validation result was 89.6% with very valid criteria. The results of the teacher's response questionnaire obtained a score of 92%, while the results of the student response questionnaire obtained a score of 91%, the average practicality value was 91.5% with very practical criteria. Meanwhile, the results of the product effectiveness test showed that there was a significant difference between the pre-test and post-test values. The average value of the students' pre-test was 77.6 and the average post-test score was 88%. The data shows that the post-test value is higher than the pre-test value and is above the KKM value that has been determined, namely 75. Based on the results of the data analysis that has been done, it can be concluded that the product that has been developed can be said to be very valid, very practical and effective. used for science learning on ecosystem material for fifth grade elementary school students. Keywords: Multimedia, Picture Guessing Game, Science Learning Abstrak: Penelitian ini dilatarbelakangi adanya permasalahan dalam penggunaan media pembelajaran dalam pembelajaran IPA pada materi ekosistem di SDN Mrican I. Tujuan dalam penelitian ini adalah untuk mengembangkan multimedia pembelajaran berbasis permainan tebak gambar pada materi ekosistem untuk siswa Kelas V SDN Mrican 1. Penelitian ini menggunakan model pengembangan ADDIE yang mempunyai lima tahapan di antaranya: Analysis, Design, Development, Implementation, dan Evaluation. Kualitas peneltian ini dilihat dari tingkat kevalidan, kepraktisan dan keefektifan dari produk yang dikembangkan. Adapun hasil penelitian dan pengembangan terkait data hasil validasi ahli media mendapat skor 91,7%, sedangkan validasi oleh ahli materi IPA SD memperoleh skor 87,5%, rata-rata hasil validasi adalah 89,6% dengan kriteria sangat valid. Hasil angket respon guru memperoleh skor 92%, sedangkan hasil angket respon siswa memperoleh skor 91% rata-rata nilai kepraktisan adalah 91,5% dengan kriteria sangat praktis. Sedangkan hasil uji keefektifan produk menunjukkan adanya perbedaan yang signifikan antara nilai pre-test dan nilai post-test. Nilai rata-rata pre-test siswa sebesar 77,6 dan nilai rata-rata skor post-test sebesar 88%. Data tersebut menunjukkan bahwa nilai post-test lebih tinggi dari nilai pre-test dan berada di atas nilai KKM yang telah ditentukan yaitu 75. Berdasarkan hasil analisis data yang telah dilakukan dapat disimpulkan bahwa produk yang telah dikembangkan dapat dikatan sangat valid, sangat praktis dan efektif digunakan untuk pembelajaran IPA materi ekosistem siswa Kelas V SD. Kata Kunci: Multimedia, Permainan Tebak Gambar, Pembelajaran IPA